2020
DOI: 10.1097/tp.0000000000003025
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Obesity in Childhood Solid-Organ Transplant Recipients

Abstract: Background. Obesity is a significant public health concern; however, the incidence post solid-organ transplantation is not well reported. Methods. This study determined the incidence and risk factors of obesity among pediatric solid-organ transplant recipients (heart, lung, liver, kidney, multiorgan) at The Hospital for Sick Children (2002–2011), excluding prevalent obesity. Follow-up occurred from transplantation until development of obesity, last foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Immunosuppressive medication is likely to contribute to the risk of cardiovascular morbidity by increasing the likelihood of hypertension, dyslipidemia, and diabetes mellitus 11 . A recent study among pediatric transplant recipients showed that 25% of the recipients were obese at 5 years after transplantation 12 . Physical performance evaluation should be an important part of the posttransplant follow‐up addressing the problem of low physical activity (PA) and physical deconditioning in pediatric SOT recipients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressive medication is likely to contribute to the risk of cardiovascular morbidity by increasing the likelihood of hypertension, dyslipidemia, and diabetes mellitus 11 . A recent study among pediatric transplant recipients showed that 25% of the recipients were obese at 5 years after transplantation 12 . Physical performance evaluation should be an important part of the posttransplant follow‐up addressing the problem of low physical activity (PA) and physical deconditioning in pediatric SOT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…11 A recent study among pediatric transplant recipients showed that 25% of the recipients were obese at 5 years after transplantation. 12 Physical performance evaluation should be an important part of the posttransplant follow-up addressing the problem of low physical activity (PA) and physical deconditioning in pediatric SOT recipients.…”
mentioning
confidence: 99%
“…11% in liver and 6% in heart transplant recipients). 8 Obesity is known to be proinflammatory 12 and when present at the time of transplant has been associated with multiple adverse events in pediatric kidney transplantation. First, obesity has been shown to correlate with metabolic syndrome among transplant recipients with manifestations including hypertension, dyslipidemia and glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Additionally, children who were overweight at baseline, or who were exposed to steroids, were most likely to develop obesity post-kidney transplantation. 8 Finally, obesity has also been associated with worse post-transplant outcomes including increases in rates of delayed graft function (DGF), acute rejection and increased hospitalizations as well as decreased graft, and patient survival. 7,[15][16][17] With regard to undernutrition, chronically ill children in general are at higher risk for undernutrition with one study finding that greater than 30% of chronically ill children attending outpatient visits are malnourished.…”
Section: Introductionmentioning
confidence: 99%
“…After kidney transplantation, children are at risk for developing obesity, diabetes, and hypertension, all of which can contribute to cardiovascular risk and are associated with LVH. 2,7,22,23 Longitudinal assessment of early cardiac remodeling in a large pediatric population will help determine whether the restoration of kidney function impacts cardiac structure and function and how to best manage cardiovascular health to mitigate long-term risk. The objective of this study was to investigate the influence of blood pressure management on the longitudinal changes in cardiac structure and function in pediatric kidney transplant recipients to determine patterns in cardiovascular remodeling following transplantation.…”
mentioning
confidence: 99%